Qualitative parameters of complex part produced by additive approach - Monkova, Katarina; Monka, Peter (2017 8th International Conference on Mechanical and Aerospace Engineering (ICMAE), 2017)
Considering the expansion of new trends in production technologies, it is necessary to know as much as possible effects that influence quality of produced component. Sintering of metal powder brings many problems which is necessary to identify and consequently to solve. It is more important, if the parts are complex with thin walls and it is supposed that it will be used in the equipment with high safety factor, e.g. in aerospace industry. The article deals with the base study of qualitative parameters of complex part produced from steel by additive approach. Within the research, a complex component was designed so to include many specific geometrical units that represent the most used features of technical parts. During preliminary research, two observed parameters were investigated: surface roughness and precision. From the beginning of the study it was clear that the surface will not be smooth with low surface roughness due to the principle of technology. In accordance with this prediction, the results also showed relative big differences between parameters measured in various points of the investigated areas.